2017
DOI: 10.1515/plua-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Networks have Effects on the Risk Attitude of Commercial Poultry Farmers? Evidence from Southwest Nigeria

Abstract: Abstract. Poultry production decision setting is full of risk and imperfect information. Attitude towards risk is a measure of farmers' willingness to take risks which is an important determinant in their production decisions. Strong social capital emanating from social networks can lead to efficient risk management strategies, thereby minimizing risks faced by the farmers. Therefore, the effects of social capital on the risk attitude of small-scale commercial poultry farmers in Oyo state were assessed. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This is an indication that most of the farmers are literate with higher levels of critical reasoning and problem solving capacity. This is similar to findings of Obayelu et al (2017) of literacy tend to be more efficient in production and readily accept innovation when compared with the illiterate ones that rely on only their experience. Results further show that the mean years of experience in poultry production was 10 years.…”
Section: Selected Personal and Enterprise Characteristicssupporting
confidence: 85%
See 2 more Smart Citations
“…This is an indication that most of the farmers are literate with higher levels of critical reasoning and problem solving capacity. This is similar to findings of Obayelu et al (2017) of literacy tend to be more efficient in production and readily accept innovation when compared with the illiterate ones that rely on only their experience. Results further show that the mean years of experience in poultry production was 10 years.…”
Section: Selected Personal and Enterprise Characteristicssupporting
confidence: 85%
“…Farmers' challenges and risks can be decreased by increasing the efficiency of poultry management through strong social capital from social networks. This is because social networks encourage dissemination of agricultural innovation (Adeniyi et al, 2021;Kansanga et al, 2020;Obayelu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 showed that male farmers were dominant (about 62%) in the egg-farming sub-sector of the livestock industry in the study area (in agreement with the findings of Iheke and Igbelina, 2016), majority (over 60%) of whom were within the active age group of 30-60 years with a mean value of 40  15 years. About seventy-four (74%) of the poultry farmers had acquired post-primary school education (in consonance with Obayelu et al, 2017), and married (64%) with mean household size of 4  2 persons. The mean flock size of poultry farmers in the study area was 524  327 birds (layers stock only), each farmer having been involved in active poultry egg farming for an average of 6  5 years, with an average gross income of $4,138 per egg 4 production cycle.…”
Section: Demographic and Farm-level Characteristics Of The Respondent...mentioning
confidence: 94%